Rancang Bangun Inverter Menggunakan IC CD4047 INPUT Batrai 12 VDC Ke Output Lampu 220 VAC Frekuensi 50-60 HZ - Andre Saputra; Fadli Eka Yandra (Universitas Batanghari Jambi, 2019)
Inverter is an electronic device that functions to change current direct (DC) into alternating current (AC) with the magnitude of the voltage and frequency can be adjusted, the output of an inverter in the form of AC voltage in the form of a square wave. Then testing with different types of Step Up CT transformers to get the test results and analysis. And the working principle of this inverter circuit is that the TIP122 and 2N3055 Transistor driver pulses are generated by the IC CD4047 pulse generator, the pulses of the Astambil Multivibrator circuit are 2 pulses with a phase that reverses 180º. The Q and Q pulses are used to provide drivers to the TIP122 and 2N3055 transistors and will induce the Step Up Transformer in turn. So the Step Up Transformer will be able to induce in 2 directions from the CT point. because of the induction process, the transformer primary will provide an AC voltage of 220 volts with a square wave shape. This type of inverter can only be used for lamps, the price is cheaper because it is used to back up the lamp.